Adsorptive removal of diuron on biomass ashes: a comparative study using rice husk ash and bagasse fly ash as adsorbents. Issue 47 (7th October 2016) - Deokar, Sunil K.; Singh, Diksha; Modak, Sweta; Mandavgane, Sachin A.; Kulkarni, Bhaskar D.
Abstract: This study describes the use of two types of biomass ashes (BMAs) as adsorbents for diuron removal. Two BMAs, namely rice husk ash (RHA) and bagasse fly ash (BFA), were used in this study, and their adsorption behavior and adsorption mechanism were compared based on various characteristics, such as surface area, pore diameter, and volume. It was found that the particle size and the composition of these BMAs, especially the content of carbon and silica, primarily affect the adsorption kinetics and capacity. Compared with RHA, BFA has more carbon content (47.37%), and therefore shows higher adsorption capacity (43.48 μmol/g). In addition, BFA has larger external surface area and exhibited faster kinetics at the initial adsorption stage; by contrast, RHA due to its larger pore diameter allows for faster pore adsorption and surpasses the initial kinetic rate of BFA. For the same particle size (0.354–0.251 mm), the equilibrium capacity of BFA was found to be four times greater than that of RHA; in addition, the surface area of BFA is two times more than that of RHA, suggesting that BFA has more active sites than RHA. It was found that solution pH influences adsorption mechanism of diuron molecule on BMA. The uptake capacity of BFA and RHA is 10 times greater than natural adsorbents such as soil and is comparable with synthetic adsorbents such as activated carbon and multiwalled carbon nanotubes. To our knowledge, removal of diuron using ashes has not been reported previously.